Using the cre–lox system to randomize target gene expression states and generate diverse phenotypes. Issue 10 (3rd June 2013) - Niesner, Bradley; Maheshri, Narendra
ABSTRACT Modifying the expression of multiple genes enables both deeper understanding of their function and the engineering of complex multigenic cellular phenotypes. However, deletion or overexpression of multiple genes is typically laborious and involves multiple sequential genetic modifications. Here we describe a strategy to randomize the expression state of multiple genes in Saccharomyces cerevisiae using Cre–loxP recombination. By inserting promoters flanked by inverted loxP sites in front of a gene of interest we can randomly alter its expression by turning it OFF or ON, or between four distinct expression states. We show at least 6 genes can be randomized independently and argue that using orthogonal loxP sites should increase this number to at least 15. Finally, we show how combining this strategy with mating allows easy introduction of native regulation as an additional expression state and use this to probe the role of four different enzymes involved in base excision repair in tolerance to methyl methane sulfonate (MMS), a genotoxic DNA alkylating agent. The set of vectors developed here can be used to randomize the expression of both heterologous genes and endogenous genes, and could immediately prove useful for metabolic engineering in yeast. Because Cre–loxP recombination works in many organisms, this strategy should be readily extendable. Biotechnol. Bioeng. 2013;110: 2677–2686. © 2013 Wiley Periodicals, Inc.